Workplace Lifestyle Factors and Depressive Symptoms: A Study of Japanese Organizations - Masahito Fushimi (Disease and Health: Research Developments Vol. 5, 2025)
Background: Mental illness, especially depression or the depressive state, inflicts great psychological distress on individuals and even entire neighborhoods and is a major problem influencing social life. Aim: This study aims to examine the relationship between depressive symptoms and lifestyle-related factors. Methods: The information presented in this report was collected as part of the Northern-Japan Occupational Health Promotion Centers Collaboration Study for Mental Health (NOCS-MH) for the occupational health promotion centers of the six administrative divisions located in the prefectures of northern Japan (Hokkaido, Aomori, Iwate, Miyagi, Akita, and Yamagata prefectures). A total of 2,220 employees (1,069 for males and 1,151 for females) in Japan completed the screening test of the Center for Epidemiologic Studies Depression Scale (CES-D). The cutoff point for the CES-D scores was 16 or above (high scorers). Statistical analyses were performed to analyse the collected data. Results: The identified factors that showed significant effect from the binomial multivariate logistic regression for high scorers were as follows: “habits of having breakfast” in all participants (OR = 0.78, 95% CI: 0.64–0.95); “have good eating habits” in females (OR = 0.64, 95% CI: 0.48–0.86) and all participants (OR = 0.75, 95% CI: 0.62–0.91); “satisfaction with sleep” in males (OR = 0.49, 95% CI: 0.37–0.64), females (OR = 0.47, 95% CI: 0.36–0.61), and all participants (OR = 0.46, 95% CI: 0.39–0.56); “smoking habits” in females (OR = 1.45, 95% CI: 1.06–1.99); “daily alcohol consumption” in males (OR = 0.63, 95% CI: 0.48–0.82) and all participants (OR = 0.64, 95% CI: 0.52–0.78); “hypertension” in females (OR = 0.61, 95% CI: 0.38–0.99); “periodontal disease” in all participants (OR = 1.53, 95% CI: 1.00–2.34); “history of medication” in females (OR = 1.39, 95% CI: 1.07–1.79) and all participants (OR = 1.28, 95% CI: 1.07–1.55). Conclusion: A healthy lifestyle was found to be a factor related to the depressive symptoms of the Japanese employees. The limitation of this study lies in its cross-sectional design, which makes it difficult to determine whether the correlation associated with psychological distress is an antecedent or a consequence of depressive symptoms. In order to make inferences with regard to causality, a longitudinal follow-up study will be needed in future. Future studies should focus on evaluating the importance of lifestyle in preventing depressive disorders.